USING THE AHE METHOD TO IMPROVE CHILDRENS READING SKILLS - Fajhriani, Dyla; Jariah, Nurul; Novita Sari, Yulia; Oktaviani, Winda; Dwi Januarti, Ulfah; Nasrul, Febriyeni (Al-Ashr : Jurnal Pendidikan dan Pembelajaran Dasar, 2025)
Reading is crucial when children enter elementary school. This contrasts with researchers' observations that many students in grades 1, 2, 3, and even 6 experienced reading difficulties before joining AHE. When parents taught them, children often complained about not being able to do so, even though second-grade material already requires children to understand the lesson. The purpose of this study was to determine the extent to which the AHE method improves children's reading skills. The researchers employed qualitative research methods, conducting observations, interviews, and documentation. The results showed that the AHE method was effective in improving children's reading skills.